High level of fecal calprotectin at age 2 months as a marker of intestinal inflammation predicts atopic dermatitis and asthma by age 6. Issue 5 (May 2015) - Orivuori, L.; Mustonen, K.; de Goffau, M. C.; Hakala, S.; Paasela, M.; Roduit, C.; Dalphin, J.‐C.; Genuneit, J.; Lauener, R.; Riedler, J.; Weber, J.; von Mutius, E.; et al.
Summary Background Gut microbiota and intestinal inflammation regulate the development of immune‐mediated diseases, such as allergies. Fecal calprotectin is a biomarker of intestinal inflammation. Objective We evaluated the association of early‐age fecal calprotectin levels to the later development of allergic diseases in children from farming and non‐farming environments and further studied the effect of gut microbiota on the fecal calprotectin levels. Methods Fecal calprotectin was measured from 758 infants participating in the PASTURE study at the age of 2 months using the ELISA method. Serum‐specific IgE levels were measured at 6 years of age. Data of environmental factors, doctor‐diagnosed atopic dermatitis (AD) and asthma were collected by questionnaire. Multivariate logistic regression models were used for analysis. The composition of fecal microbiota was analysed in a subgroup of 120 infants with 16S rRNA pyrosequencing. The effect of Escherichia coli lipopolysaccharide (LPS) on in vitro monocyte IL‐10 secretion was studied by flow cytometry. Results The infants with high fecal calprotectin levels at 2 months, that is above the 90th percentile, had an increased risk of developing AD and asthma/asthmatic bronchitis by the age of 6 years (aOR 2.02 (1.06–3.85) and 2.41 (1.25–4.64), respectively). High fecal calprotectin levels correlated negatively with fecal Escherichia. LPS from E. coli stimulated production of IL‐10 in monocytes. Conclusion and Clinical Relevance High degree intestinal inflammation at 2 months of age, detected as high fecal calprotectin, predicted asthma and AD by the age of 6 years and was linked to low abundance of fecal Escherichia. Impaired IL‐10 activation due to the lack of colonization with E. coli could explain the intestinal inflammation associated high fecal calprotectin and later risk of asthma and AD. Our results have implications for the design of probiotic treatments and suggest that early intestinal colonization has long‐term health effects.